Ibu-Bijak: Teknologi Penganggaran dalam Memenuhi Gizi untuk Pencegahan Stunting di Kota Tangerang - Lestari, Indah Rahayu; Oktaviani, Retno Fuji; Rahmat, Hayatul Khairul; Akilah, Maysa; Nayadi, Armetha; Setiawati, Suci; Amelia, Rini (Penerbit Goodwood, 2025)
Purpose: The purpose of this community service is to strengthen family financial literacy and nutritional awareness through the development and implementation of the Wise-Mother System a digital budgeting platform designed to help families manage household finances while ensuring balanced nutrition to prevent stunting in Tangerang City. Methodology/approach: The system adopted a participatory approach consisting of several stages, a preliminary survey and needs assessment, system design and installation, training and simulation, public socialization, and intensive mentoring. Data collection was conducted through interviews, pre-test and post-test, and field observations. Results/findings: The implementation of the Wise-Mother System successfully improved participants literacy in both financial management and nutrition. Post-test results showed a 46% improvement in budgeting skills and a 14% increase in nutritional literacy compared to pre-test scores. Furthermore, 100% of participants recognized the importance of allocating family budgets for nutritious food and understood how to use technology to support this goal. Conclusion: The Ibu Wise-Mother proved to be an effective digital innovation for empowering families to manage their household finances while improving family nutrition. Through education, training, and mentoring, the program successfully raised awareness and enhanced participants’ ability to plan family budgets aligned with nutritional needs. Limitations: The main limitations include uneven digital literacy among participants, limited internet access in certain areas, and a relatively short training duration, which required additional mentoring for consistent application of the system. Contribution: This program contributes to community development by integrating financial technology with family nutrition education, supporting the national stunting reduction agenda.